ANALISIS PREDIKSI KEBANGRUTAN BANK UMUM DAN PERSERO DI INDONESIA - , (Bilancia : Jurnal Ilmiah Akuntansi, 2018)
One of the strengths of the Indonesian economy is based on the real sector. Micro, Small and Medium Enterprises (MSMEs) are one part of the real sector that is believed to have the ability to sustain Indonesia when the global financial crisis hit the world in the past years. The purpose of this study was to find out and analyze the influence of the Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Operational Income Operating Costs (BOPO), Return On Assets (ROA) on bankruptcy of commercial banks in Indonesia. The population in this study is all financial report data of the National Commercial Banks in OJK (Financial Services Authority). While the selection of samples using Non-probability sampling which is purposive sampling. Which means that the population will be used as research samples with certain criteria. The data analysis technique in this study uses quantitative descriptive analysis and multiple linear regression analysis with the help of SPSS software. The results in this study show that the NPL variable is significantly positive for bankruptcy of commercial banks. Positive significant CAR variable for bankruptcy of Commercial Banks. LDR is significantly positive for bankruptcy of Commercial Banks. ROA is significantly positive for bankruptcy of Commercial Banks. BOPO (Operational Cost of Operational income) has a positive effect on bankruptcy of Commercial Banks. Kekuatan perekonomian Indonesia salah satunya dilandasi oleh sektor riil.Usaha Mikro Kecil dan Menengah (UMKM) merupakan salah satu bagian dari sektor rill yang diyakini memiliki kemampuan dalam menopang Indonesia ketika kondisi krisis keuangan global melanda dunia pada periode tahun-tahun terakhir. Tujuan penelitian ini untuk mengetahui dam menganalisis pengaruh Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Biaya Operasional Pendapatan Operasional (BOPO), Return on Aset (ROA) terhadap kebangkrutan bank umum di Indonesia. Populasi dalam penelitian ini adalah seluruh data laporan keuangan Bank UmumNasional  Yang ada di OJK (Otoritas Jasa Keuangan). Sedangkan pemilihan sampel menggunakan Non-probability sampling ini menggunakan carapurposive sampling. Yang berarti bahwa populasi yang akan dijadikan sample penelitian dengan kriteria tertentu.Tekniuk analisis data dalam penelitian ini mengunakan analisis deskriptif kuantitatif dan analisis regresi linier berganda dengan bantuan software SPSS. Adapun hasil dalam penelitian ini menunjukan bahwa variabel NPL signifikan positif terhadap kebangkrutan Bank Umum.Variabel CAR signifikan Positif terhadap kebangkrutan Bank Umum. LDR signifikan positif terhadap kebangkrutan Bank Umum.ROA signifikan positif terhadap kebangkrutan Bank Umum. BOPO (Biaya Operasional terhadap pendapatan Operasional) berpengaruh secara positif terhadap kebangkrutan Bank Umum.